Assessing the impact of information technology on human resource practices: evidence from organisations in Ghana. (29th March 2021) - Attatsitsey, Mayqueen; Osei-Bonsu, Noble
Information technology (IT) is universally regarded as an essential tool in enhancing the competitiveness of the economy of a country. There is consensus that IT has significant effects on the productivity of firms. This study focused on how modern information technology impacts on effectiveness and efficiency of HR practices. Human resource management (HRM) practitioners generally use IT in the form of a human resource information system (HRIS) for the purposes of decision-making in the field of HR. The main objective of this study was to examine the impact of IT on HR practices in organisations in Ghana. 100 organisations were purposively sampled for the study. The descriptive survey methodology was used. Data was collected using a self-designed questionnaire made up of closed and open-ended questions and statements. Results revealed organisations awareness and use of the various HR-related software, and despite the fact that these software programs are costly, they, at the same time, generate terrific benefits.